The implementation of Natura 2000 in forests: A trans- and interdisciplinary assessment of challenges and choices. Issue 52 (October 2015) - Winkel, Georg; Blondet, Marieke; Borrass, Lars; Frei, Theresa; Geitzenauer, Maria; Gruppe, Axel; Jump, Alistair; de Koning, Jessica; Sotirov, Metodi; Weiss, Gerhard; Winter, Susanne; Turnhout, Esther
Highlights: This paper analyses the implementation of Natura 2000 in forests. An inter- and transdisciplinary approach is used. Five important challenges and five possible policy pathways are identified. A combination of the pathways is recommended to advance Natura 2000 implementation. Abstract: Natura 2000 is the core of the EU's biodiversity conservation policy. 50% of the overall protected area under Natura 2000 is forest. Yet, comparatively little is known about the implementation of the policy in forests. Building on a rich set of social and natural science data, and an inter- and transdisciplinary discussion process involving scientists from different disciplines as well as EU, national and local stakeholders, this paper identifies five important challenges related to the implementation of Natura 2000 in forests: (1) the balancing of biodiversity conservation and timber production, (2) the integration of conservation (science) and local stakeholders' demands, (3) climate change, (4) lacking and less effective funding, and (5) conflicts related to other sectoral policies. Subsequently, five possible pathways to tackle these challenges are proposed: (1) a learning approach through better communication and transparency, (2) a pathway emphasizing the role of conservation science in developing management strategies and responding to climate change, (3) an approach of better integrating Europe's citizens in the design and implementation of the policy, (4) an approach highlighting the necessity of an effective funding strategy, and (5) the vision to work towards an integrated European land use and conservation policy. In conclusion, we emphasize, on one hand, the distinct character of the five pathways but, on the other hand, underline that probably all of them need to be followed in order to make the implementation of Natura 2000 in Europe's forests a success story.